Influenza virus infection expands the breadth of antibody responses through IL-4 signalling in B cells - Miyauchi, Kosuke; Adachi, Yu; Tonouchi, Keisuke; Yajima, Taiki; Harada, Yasuyo; Fukuyama, Hidehiro; Deno, Senka; Iwakura, Yoichiro; Yoshimura, Akihiko; Hasegawa, Hideki; Yugi, Katsuyuki; Fujii, Shin-ichiro; et al. (Nature communications, 2021)
Influenza viruses are a major public health problem. Vaccines are the best available countermeasure to induce effective immunity against infection with seasonal influenza viruses; however, the breadth of antibody responses in infection versus vaccination is quite different. Here, we show that nasal infection controls two sequential processes to induce neutralizing IgG antibodies recognizing the hemagglutinin (HA) of heterotypic strains. The first is viral replication in the lung, which facilitates exposure of shared epitopes that are otherwise hidden from the immune system. The second process is the germinal center (GC) response, in particular, IL-4 derived from follicular helper T cells has an essential role in the expansion of rare GC-B cells recognizing the shared epitopes. Therefore, the combination of exposure of the shared epitopes and efficient proliferation of GC-B cells is critical for generating broadly-protective antibodies. These observations provide insight into mechanisms promoting broad protection from virus infection. The reasons why influenza infection promotes a broader antibody response compared with vaccines are not fully understood. Here the authors show that unmasking of haemagglutinin epitopes and IL-4 signals in the germinal centre contribute to broader antibody responses after infection.